1994
DOI: 10.1289/ehp.94102290
|View full text |Cite
|
Sign up to set email alerts
|

Polychlorinated biphenyls as hormonally active structural analogues.

Abstract: Among the environmental chemicals that may be able to disrupt the endocrine systems of animals and humans, the polychlorinated biphenyls (PCBs) are a chemical class of considerable concern. One possible mechanism by which PCBs may interfere with endocrine function is their ability to mimic natural hormones. These actions reflect a close relationship between the physicochemical properties encoded in the PCB molecular structure and the responses they evoke in biological systems. These physicochemical properties … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
173
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 295 publications
(178 citation statements)
references
References 46 publications
5
173
0
Order By: Relevance
“…Avian species are variable in their sensitivity to PCB congeners, but it has been well established that coplanar dioxin-like congeners such as PCBs 77, 81, and 126 induce toxicity at higher rates than non-dioxin-like congeners [4][5][6][7][8]. Recent contaminant analysis has shown that concentrations of PCBs 77, 81, and 126 account for approximately 86, 9, and 3% respectively, of the total PCB toxic equivalents (TEQs) in tree swallow eggs collected along the Upper Hudson River in 2004 [9].…”
Section: Introductionmentioning
confidence: 99%
“…Avian species are variable in their sensitivity to PCB congeners, but it has been well established that coplanar dioxin-like congeners such as PCBs 77, 81, and 126 induce toxicity at higher rates than non-dioxin-like congeners [4][5][6][7][8]. Recent contaminant analysis has shown that concentrations of PCBs 77, 81, and 126 account for approximately 86, 9, and 3% respectively, of the total PCB toxic equivalents (TEQs) in tree swallow eggs collected along the Upper Hudson River in 2004 [9].…”
Section: Introductionmentioning
confidence: 99%
“…Many of the biological effects observed for PCBs are due to their ability to mimic hormones such as thyroid and steroid hormones [31][32][33]. Planar PCBs congeners, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…nonortho-substituted biphenyls, are high-affinity ligands for the aromatic-hydrocarbon (Ah) receptor while the non-planar PCB congeners, i.e. ortho-substituted biphenyls, display no or weak affinity for the Ah-receptor [31]. Some of the toxicity observed for PCBs involves reproductive toxicity [31], immunotoxicity [34], neurotoxicity [35] as well as induction of hepatic xenobiotic-metabolizing enzymes [36].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies investigating the mechanisms of action underlying the effects of PCBs on endocrine tissues revealed that PCBs can interfere with steroido genesis and steroid receptors (McKinney and Waller, 1994) and with the mixed-function oxygenase systems involved in steroid metabolism (Goksoyr and Forlin, 1992), and are able to bind to the Ah receptor (Nebert, 1989). PCBs may interfere with corticosteroidogenesis and corticosteroid action in a similar manner as de scribed for gonadosteroidogenesis (Barron et al, 1995) and thyroid hormone synthesis (McKinney and Waller, 1994;Murk et al, 1994). Little information is available, however, on PCB effects on adrenal function, in particu lar during stress.…”
Section: Introductionmentioning
confidence: 99%